IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH NOMOR 07 TAHUN 2016 TERHADAP MANAJEMEN PENGELOLAAN SAMPAH KABUPATEN SIDENRENG RAPPANG - Ilviani Ilviani; Monalisa Ibrahim; Ahmad Mannu; Rahman Yaqub (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aims to determine the implementation of the regional policy of 2016 waste management regulation at Sidenng Rapang Regency, and to find out what factors influence the implementation of the 2016 regional policy on the management of waste management. The population in this study was 319.990 people in Sidenng Rappang Regency, where sampling was used with a probability of sampling with a simple random sampling technique using the Slovine formula with a total sample of 106. Information collection techniques Used were observations, questionnaires, interviews, revision of literature. . The information analysis technique used are descriptive statistics, linear regression, hypothesis test using SPSS 16.0 and a Likert scale. The results of this study show that the effect of policy implementation variables on management management is 55.4%, a. Communication with interpretation 54.8%, resources 50.8%, 51% arrangement / attitude, bureaucratic structure 52.2%, categorized as is not good, while waste management has been classified, b. Planning of 53.8%, organizing 55.6%, which works 54.2% and supervision of 52.8% with the